The development of higher education in Africa prospects and challenges - Wiseman, Alexander W. 1968-; Wolhuter, C. C. (Emerald, 2013)
The global education revolution of the 20th century resulted in massive developments in education worldwide, but the higher education sector throughout Africa remains surprisingly underdeveloped. Although impressive expansion and reform of higher education in Africa have occurred since 1990, the higher education sector across Africa has been particularly challenged to keep pace with the development of higher education worldwide. This is reflected in comparatively limited research output by African university scholars and researchers and the limited representation of African universities on world institutional rankings. Given both the perceived and real gap in research productivity and scholarly reputation between African higher education and higher education systems in other parts of the world, the question persists whether or not the African higher education sector can produce "world-class" universities.
Includes indexes.